PENERAPAN METODE SNOWBALL THROWI Penerapan Metode Snowball Throwing untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa di Sekolah Menengah Pertama - Rinah, Rinah (Institut Teknologi Pendidikan Indonesia, 2023)
The aim of this research is to improve the learning outcomes of Islamic religious education through the snowball throwing method for junior high school students. This research is a Classroom Action Research (CAR) which is carried out in each learning cycle consisting of planning, implementing, observing, and reflecting. The subjects of this study were class VII students of SMP Negeri 8 Pekanbaru. Data collection techniques included observation sheets, worksheets and documentation. From the results of data analysis for two cycles showed that out of17 students: there was an increase in student learning outcomes based on cycle I the averagestudent score was 64.11 with classical completeness 41.18%. Then after improving learning cycle II, the average student score increased to 80.59 with classical completeness of 88.23% or an increase in the average student score of 16.48 with an increase in classical completeness of 47.05%. Based on the discussion of research results and data analysis, it can be concluded that there was an increase in learning outcomes and students' understanding also increased after the application of the snowball throwing learning method.